Are stock markets of emerging economies informationally efficient? Causal analysis of stock prices and macroeconomic variables of EM7 economies for the recent decade - Mearaj-ud-Din DAR; Khursheed Ahmad BUTT (Theoretical and Applied Economics, 2023)

(untitled)
An informationally efficient stock market is one of the indispensable factors for the smooth working of the economic machinery of a country. Efficient market hypothesis in this regard provides the theoretical base, which eliminates the possibility of beating the market and provides a level playing field for everyone in the market without any intervention. The informational efficiency of the major stock markets throughout the globe has been extensively researched by examining the causal links between stock prices and macroeconomic indicators. However there is considerable gap with respect to emerging stock markets. Therefore present study is an attempt to examine the efficiency of the stock markets of EM7 (India, China, Brazil, Russia, Indonesia, Mexico, and Turkey) which are going to be the epicentre of investment and growth in the coming times. Granger Causality Test is applied on monthly time series data for the recent decade spanning from 2010 to 2019. The study has found major directional relationships as unidirectional particularly running from macroeconomic variables to stock prices. The results of the study indicate that stock markets of the EM7 largely inefficient in terms of fundamental macroeconomic variables which in turn provide scope to reap abnormal returns by having prior information on macroeconomic front. The results indicated Chinese stock market as comparatively efficient among sample countries.